Uncertainty and COVID-19: A turning point for Monitoring Evaluation, Research and Learning? - A discussion note for aid actors, policymakers and practitioners - Tyrrel, Lavinia; Roche, Chris; Jackson, Elisabeth (Abt Associates, 2020)
The COVID-19 pandemic has significantly shifted the context in which aid and development is being delivered. The global scale of the pandemic and the speed at which it is spreading mean that the ‘normal’ economic, ideological and organisational influences which shape (if not determine) aid delivery are in flux. This means that – for a relatively short-period – there is scope for aid actors to work collectively to embed more locally-led, politically-informed and adaptive forms of MERL in aid and development practice. These forms of Monitoring Evaluation Research and Learning (MERL) are not only well-suited to the current global pandemic. They also offer ways for aid program decision makers and practitioners to make sense of the complex and uncertain contexts in which much development work takes place. Applying locally-led, politically-informed and adaptive forms of MERL in the COVID-19 context and beyond requires a shift in mindset and approaches. Situations of complexity, in which it is difficult to predict the relationships between cause and effect, do not lend themselves to linear approaches and fixed indicators. Instead, they require ‘navigation by judgement’, ongoing learning and adaptation and greater privileging of local knowledge, and of the perspectives of those who are often excluded. Rather than being focused on upwards accountability, simple numbers and good news stories, the core function of MERL in this context is to support a better understanding – in real-time – of the changing operating context, to generate learning about the immediate impact of policy and program responses and their longer-term effects, and to inform decision making by front line staff. Whether the opportunities afforded by this ‘critical juncture’ are realised will depend on the degree to which those in the aid and development sector use this opportunity to promote a shift in the deep incentive structures within which development agencies are embedded. On the one hand, the pandemic underscores the limits of the linear understandings of change which underpin many orthodox approaches to planning, design and associated MERL. On the other hand, there is a vested interest in the status quo amongst many organisations, consultants, researchers and MERL practitioners. This is because approaches which promote locally-led development inevitably require those in power to relinquish control. While a range of factors make this shift difficult, there is more scope to change internal ways of working in development agencies than is commonly acknowledged. There is no time like the present to advocate for a ‘new normal’ for MERL.

The Hidden Life of Theories of Change - Ho, Wenny; Tamas, Peter; van Wessel, Margit (Hivos, 2020)
Theory of Change is thought to be very useful for learning and adaptive management of complex interventions such as advocacy. Nevertheless, the use of Theory of Change is also under critique. One common criticism is that Theory of Change is often used as a framework that fixes agreements rather than as a living, guiding tool that helps reflection and adaptation. However, while such criticism stresses forms of control, little research has looked at the way Theory of Change and advocacy practice relate. This is a pertinent issue considering that formally agreed Theories of Change and realities on the ground can be very different. This raises questions: Do advocates work in ways different from what Theory of Change states, and if so, how, and why? How does the way they strategize relate to formal Theories of Change? With what implications? In this brief, we explore these more hidden aspects of the life of Theories of Change.